ANALYSIS OF CINAPEL BRIDGE PROJECT CONSTRUCTION MANAGEMENT ON THE CISUNDAWU TOLL ROAD - Nopa Pahlawati; Nikko Rozy; Saihul Anwar (Journal of Green Science and Technology, 2019)
ABSTRACTConstruction management is an attempt to use limited resources efficiently, effectively and timly in completing a project that has been palnned. There are 3 kinds of basic functions of construction management including planning, implementation, and control. Of three of these activities to control the resources on aproject that includes worker, equipment, material, money, and method.The research method used was qualitative research, as a way of collecting data on the study is how the study of the literature, interviews and direct observation in field. And this method is a method that is done to get a foundation theory in analyzing data, namely the analysis calculation of the volume of material, analysis of labor, analysis tool, method, method of Bar Chart S Curve and Critical Path Method.The location of the studies reviewed were Analysis Of Cinapel Bridge Project Construction Management On The Toll Cisundawu Road, located on Pamatutan Hamlet Mulyasari â€“ Pasir Hamlet Margamukti, Sumedang. The results of this research is the budget plan costs Â completed the construction of the Cinapel Bridge Project on Cisundawu Toll Road until the final stage costs less than Rp. 168,020,632,320, - and analysis of the Critical Path Method (CPM) estimates that the completion of the Cinapel Bridge on Cisundawu Toll Road takes 129 weeks (903 days)Keywords: Construction Management, Bar Chart, S Curve, Critical Path Method